Периодические и ограниченные па плоскости решения систем гиперболических уравнений - Асанова, А.Т.; Джумабаев, Д.С. (Український математичний журнал, 2004)
Для лінійної системи гіперболічних рівнянь другого порядку з двома незалежними змінними досліджено питання існування та єдиності періодичного за обома змінними розв'язку і періодичного за однією із змінних обмеженого па площині розв'язку. Методом уведення функціональних параметрів отримано достатні умови однозначної розв'язності розглядуваних задач. For a linear system of hyperbolic equations of the second order with two independent variables, we investigate the problem of the existence and uniqueness of a solution periodic in both variables and a solution periodic in one of the variables and bounded on a plane. By using the method of introduction of functional parameters, we obtain sufficient conditions for the unique solvability of the problems under consideration.